Mītsāqan Ghalīẓan and Unregistered Marriage: Reinterpreting Contemporary Islamic Jurisprudence through Takhrīj al-Ḥadīth - Shaleh, Ibnu; Hayati; Daud, Anwar; Nufiar; Embong, Rahimah (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2026)
This study stems from the contradiction between the concept of mitsāqan ghalīẓan as a strong marital bond and the continued prevalence of unregistered marriages, which have the potentian to disregard the protection of the civil rights of husbands, wives, and children. This study aims to analyze the authenticity of hadiths on marriage (munakahat) through takhrij al-hadith and to examine their implementation from a contemporary fiqh perspective based on the empirical reality of unregistered marriages. This study employs a qualitative method whit a normative-empirical approach that combines literature review and field research through interviews and observations. Normative data were obtained from hadiths in the Kutub al-Tis’ah, fiqh Literature, and legislation, while empirical datawere obtained from the Head of the Religious Affairs Official (KUA), religious counselors, community leaders, religious figures, village imams, and those involved in informal marriages in Suro Makmur Subdistrict, Aceh Singkil Regency. The research results indicate the the hadith regarding the giardian, witnesses, and the public announcement of marriage are classified as ṣaḥīḥ li ghairihi or ḥasan li ghairihi, thereby emphasizing the importance of transparency in marriages contracts. Field findings indicate that the practice of informal marriages is generally influenced by underage marriage, administrative obstacles, economic factors, and family-related social issues. Differences in perspective between KUA officials and religious leaders also reveal a gap between the validity of classical fiqh and the need for modern legal protection. This study concludes that marriage registration constitutes an implementation of maṣlaḥah mursalah and aligns with objectives of maqāṣid al-syarī‘ah in protecting religion, lineage, honor, and the civil right of the family; thus, the practice of unregistered marriages is no longer relevant to maintain in the context of a modern rule-of-low state.